The Distribution of Van Hiele Levels of Geometrical Thought for students of the educational qualification diploma and its relationship to reading comprehension in engineering (Field study at the Faculty of Education at Tishreen University) - نصور, رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study aimed to determine the distribution of van Hiele levels of geometric thinking among students and its relationship to reading comprehension, the research sample consisted of 37 male and female students of the Educational Qualification diploma in the Faculty of education at Tishreen University, the researcher used the van Hiele Geometric Reasoning Test and prepared a reading comprehension test, the results of the study showed that van Hiele 's levels of engineering thinking are divided into the five levels among students of the Educational Qualification Diploma, majoring in Mathematics, there is a positive and strong correlation between the two variables, van Hiele and reading comprehension for students, the study showed that the higher the students' scores on the van Hiele test, the higher their scores in reading comprehension, the researcher suggested reconsidering engineering courses at different educational stages and organizing them in sequence according to van Hiele 's levels of engineering thinking, and attention to developing reading comprehension skills and including it in mathematics curricula in a sequential manner